Resepsi Hadis dalam Sinetron Taqdir Ilahi: Ujian dari Allah - Sherina Wijayanti (Al-Qudwah)
This research discusses a movie titled “Taqdir Ilahi Ujian dari Allah” whose content is from Prophet Muhammad PBUH hadith. This article tries to photograph the role of hadith meditation which is presented in religious movies, where the religious proselytizing of hadith through the movie attracts the society to reconsider the hadith until the functional which is illustrated by the actors and actresses involved. The development of technology takes place transforming hadith into a form of a movie as its development, however, on the other side, it becomes harder challenging when the hadith is only visualized textually. At this point, the hadith formed into a movie has not been entirely respresenting the reality of sequences there. It’s not without cause, this happens because the divergence between the reality of people in the past to this era is inapplicable. The movie presents the delivering of Prophet PBUH hadith effectively through the scenes with actually with the chronological background in Indonesia Archipelago. The purpose of this study is to provide the occurrence of digital hadith which has shaped into the visual domain presented in the form of religious movies. The research uses the qualitative method by directly having the observation through watching the movie titled “Taqdir Ilahi Ujian dari Allah” as the primary source, then together with this, the library study is used as the secondary source which correlates to this research. This research shows first, the scenes illustrate hadith tangibly by the actors and actresses so that the society can take the wisdom. Second, the movie “Taqdir Ilahi Ujian dari Allah” reflects hadith through exegetical, aesthetic, and functional. Third, even though the movie has tried to present hadith’s, it still does not reflect the hadith entirely, but it can become the alternative for society to understand hadith easily.